The Effect Of Training On The Performance Of Civil Servants Moderated By Supervision - Marisi Butarbutar; Mhd Ramadhan; Risa Kartika Lubis; Anju Bherna D Nainggolan; Oktaviani Manurung (International Journal of Economics, Business and Innovation Research, 2025)
The purpose of this study was to examine the effect of training on the performance of civil servants moderated by supervision. The approaches applied in the research design include descriptive qualitative and descriptive quantitative approaches. The results showed that training has a positive and significant influence on employee performance, and supervision acts as a moderator in the relationship between training and performance.